Parents' Role in Biology Learning During the Covid 19 Pandemic - Desi Rahmadani; Ika Chastanti; Dahrul Aman Harahap (Postgraduate, University of Mataram, 2021)
The role of parents in accompanying children's success while studying at home is very central, in relation to this released various guidelines for parents in accompanying their children during this pandemic which includes parenting tips to be more positive and constructive in accompanying them. Parents initially played a role in guiding basic attitudes and skills, such as religious education to obey the rules, and for good habituation, but their role became expanded, namely as a companion to academic education. The aim of this research are to explain the actual role of parents in children's learning during this pandemic and to find out what children will do if there is no role of parents in children's learning during this pandemic. This research uses purposive sampling method. In this technique the researcher determines the sumpling taking according to the research objectives, so that it is expected to answer the researcher's problems. By using a qualitative approach, the data analysis technique was carried out in a descriptive qualitative manner using the Miles Damn Huberman model. The results showed that the role of parents in learning biology during the epidemic was based on educators (80%); Supervisor (75%); counselors (70%) (4) opinion on online learning (75%; the number of cities that were broadcast during the pandemic (85%).